2019
DOI: 10.3390/ijerph16081429
|View full text |Cite
|
Sign up to set email alerts
|

Time to Onset of Paresthesia Among Community Members Exposed to the World Trade Center Disaster

Abstract: We examined whether time to onset of paresthesia was associated with indicators of severity of World Trade Center (WTC) exposure. We analyzed data from 3411 patients from the Bellevue Hospital—WTC Environmental Health Center. Paresthesia was defined as present if the symptom occurred in the lower extremities with frequency “often” or “almost continuous.” We plotted hazard functions and used the log-rank test to compare time to onset of paresthesia between different exposure groups. We also used Cox regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…NHANES prevalence data from this period suggested that any WTC exposure, whether the most or the least exposed, increased by two-fold the likelihood of reporting neuropathic symptoms. This standardization to NHANES bolsters the connection between WTC exposure and paresthesia symptoms also found in previous neuropathy symptom studies [15,16,17]. Moreover, we used a validated screening questionnaire, the DNS, in addition to questions on paresthesias of the upper and lower extremities, similar to the questions used by Marmor et al [16], to examine prevalence in our population using multiple measures; therefore, giving our findings a more robust framework.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…NHANES prevalence data from this period suggested that any WTC exposure, whether the most or the least exposed, increased by two-fold the likelihood of reporting neuropathic symptoms. This standardization to NHANES bolsters the connection between WTC exposure and paresthesia symptoms also found in previous neuropathy symptom studies [15,16,17]. Moreover, we used a validated screening questionnaire, the DNS, in addition to questions on paresthesias of the upper and lower extremities, similar to the questions used by Marmor et al [16], to examine prevalence in our population using multiple measures; therefore, giving our findings a more robust framework.…”
Section: Discussionmentioning
confidence: 79%
“…To date, three previous questionnaire-based studies have investigated the prevalence and risk factors for peripheral neuropathy in smaller WTC-exposed populations and reported that neuropathy symptoms were commonly associated with WTC-related exposure or WTC cleaning work [15,16,17]. The purpose of the current study is to investigate the prevalence of self-reported peripheral neuropathic symptoms and paresthesias among more than 9000 WTC-exposed Fire Department of the City of New York (FDNY) firefighters and emergency medical workers (EMS) between 7 June 2017, when the Diabetic Neuropathy Symptom (DNS) score was added to FDNY monitoring questionnaires, and 6 April 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information is captured on type, onset and severity of numerous physical symptoms. We previously used the WTC EHC clinical database to conduct and publish research on lower respiratory symptoms (LRS) and neuropathic symptoms [ 4 , 14 , 15 , 16 , 17 , 18 , 36 ]. In addition to exposures to WTC dust and fume, the WTC survivors were also exposed to traumatic psychological exposures, and extensive data have been collected on mental health symptoms of PTSD, depression, anxiety and substance use [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The WTCHP created inclusion criteria for enrollment for treatment in this program, which required defined WTC exposures, and for community members only, the presence of a certifiable WTC-related health condition [ 4 ]. We previously showed that WTC acute and chronic exposures are significantly associated with lower respiratory symptoms (LRS), lung function abnormalities and neuropathic symptoms [ 14 , 15 , 16 , 17 , 18 ]. Moreover, our documentation of psychological exposures and relevant mental health symptoms (PTSD, anxiety and depression) allowed longitudinal mental health analysis and we showed that WTC dust exposures are associated with mental health disorders [ 19 , 20 ] as well as physical health symptoms of WTC survivors, including both adults and children [ 4 , 5 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to respiratory disease, other long term adverse health outcomes of WTC-related exposure include neurologic conditions and cancer. Papers in this issue focused on these emerging conditions including peripheral neuropathy (Colbeth, 2019 [16]), paresthesia (Thawani, 2019 [17]), and thyroid cancer (van Gerwen, 2019 [18]; Tuminello, 2019 [19], see Gargano, 2018 [20] for a review of non-respiratory physical health conditions). Two studies focused on neuropathic conditions that included peripheral neuropathy among New York City firefighters and emergency medical workers (Colbeth, 2019 [16]) and parenthesia among community survivors who received treatment at one of the WTC Health programs (Thawani, 2019 [17]).…”
mentioning
confidence: 99%